A CALORIMETRIC STUDY OF LIGHT HYDROCARBON ADSORPTION ON METAL-ORGANIC FRAMEWORKS - Barrett, Taylor Ellise (Wake Forest University, 2019)
The effect of metal-organic framework (MOF) structural modifications on C2 hydrocarbon gas adsorption was studied. Two main MOF structures were modified and tested: UiO-66, which has two types of pores in the structure and can support various functional groups on the organic linker, and MOF-74, which can support a multi-metal cluster. The adsorption of C2 hydrocarbons on UiO-66 and UiO-66 functionalized with –NH2 and –NO2 was investigated to assess the role of confinement and electrostatic potential on binding energies at 293 K. Measurements were also collected at 195 K to better resolve the binding energies of the different types of adsorption sites. Confinement effects at the adsorption site and electrostatic potential of the adsorbate both contribute to the strength of the interaction within the lattice. The adsorption behavior at low coverage suggests that an unexpected third type of binding site is present in the MOF, which was further explored by studying adsorption behavior of UiO-66 with induced missing linker defects. MOF-74 was synthesized with cobalt, nickel, copper and combinations of Cu-Co, Ni-Co, and Cu-Ni to assess the adsorption behavior of mixed-metal MOFs. In all cases, the mixed-metal MOF binding energies were either equal to or lower than the single metal MOF samples. Overall, the UiO-66 study provides new insights into the adsorption behavior of C2 hydrocarbons and the types of UiO-66 binding sites. The MOF-74 data illustrates that mixed-metal MOFs can be synthesized based on phase requirements, and that the effect of mixed metal clusters on the binding energy depends on the adsorbate.
Keywords: Calorimetry; hydrocarbons; linker functionalization; MOF; MOF-74; UiO-66